Total Lipids and Storage Quality of Oil Seeds and Nuts as Influenced by Yeast Fermentation - Anshira M. H.; Haseena Sheikh; Gunashree B. S (International Journal of Fungi, 2024)
Oilseeds and the products made from them have a role in a healthy balanced diet, even though they are energy dense and contain a high proportion of fat. Most oilseeds are made up of protein and oil. In general, fat is 18–45% by weight of oilseeds and protein is about 16–40%. Fluctuations in oil yields can cause significant fluctuations in their rates. The oils contain fat-soluble vitamins and unsaturated fats such as omega-3 and omega-6, making them nutritionally useful. It is especially important in vitamin D and E supplementation and vitamin A utilization. Several yeast strains, including the genus Pichia have been used in fermentation process of many food stuffs. In the present study, the powdered samples of oilseed and nuts such as chia seeds, flax seeds, sesame, peanuts, and almonds were fermented using two yeast strains such as Pichia fermentans and Pichia kluyveri. After fermentation the culture broth were centrifuged and the pellets containing the seed samples were dried and subjected for extraction of oil. The results showed higher oil yield with fermented samples when compared to their respective raw samples. There was significant decrease in the peroxide value of 32.5%, 15.8%, and 16.7% in peanut, almond, and flax seeds fermented with P. kluyveri, respectively, while with P. fermentans, flax seeds, and peanut showed 16.7% reduction among all the tested oil samples. However, chia seed oil showed no change between the samples when compared to its raw. Hence, yeast fermentation plays an important role in reducing the oxidative rancidity of different cooking oils and thus improving their shelf life.
Keywords: Oil seeds and nuts; Pichia fermentans; Pichia kluyveri; rancidity; yeast fermentation